The nihilism of technology in Heidegger’s Black Notebooks - Baltar, Ernesto (TECHNO REVIEW. International Technology, Science and Society Review /Revista Internacional de Tecnología, Ciencia y Sociedad, 2021)
The recent publication of the Black Notebooks offers new and relevant information that can help us better understand the evolution of the concept of technology in Heidegger's thought and its relationship with other central questions of his philosophy such as nihilism, machination, domination, history or the new beginning, among others. In this article we propose to relate these new contributions to the rest of his work.